Association Between Unpredictable Work Schedules and Depressive Symptoms in Korea - Hye-Eun Lee; Ichiro Kawachi (Elsevier, 2021)
Backgrounds: Irregular and unpredictable work schedules have become more common in most societies. The purpose of this study was to investigate the association between unpredictable work schedules and depressive symptoms in Korea. Methods: Data from 34,486 workers who participated in the Korean Working Condition Survey in 2017 were used. Unpredictable work schedules were measured by questions about the frequency of changes in work schedule and limited advanced notice. Depressive symptoms were assessed by a single item asking if the participants had depressive symptoms over the last 12 months. Multivariable-adjusted logistic regression analysis was used to calculate odds ratios (ORs) for high depressive symptoms. Results: The OR for depressive symptoms was significantly higher in the workers with unpredictable work schedules compared to those with predictable work schedules after controlling for age, sex, education, salary, marital status, occupation, contract period, full-time versus part-time, shift work, weekly working hours, and having a child under the age of 18 years (OR = 2.43, 95% confidence interval 1.93-3.07). Conclusion: Unpredictable work schedules were associated with depressive symptoms controlling for the other dimensions of precarious employment in a representative working population in Korea.